Unusual herpetic reactivation in a young female following botox injection: a case report study - Ehsan Amini-Salehi; Narges Eslami; Amirhossein Tamimi; Nasrin Sedighi; Saman Soltani Moghdam; Tofigh Yaghubi-Kalurazi; Soheil Hassanipour; Farahnaz Joukar; Fariborz Mansour-Ghanaei; Hojat Eftekhari (BMC Infectious Diseases, 2023)
Abstract Background Botox injections are commonly used for cosmetic and therapeutic purposes because they temporarily paralyze muscles, reduce wrinkles, and alleviate certain medical conditions. Although generally considered safe and effective, Botox injections may cause potential complications. While herpes reactivation is more commonly associated with immunosuppressive therapies, such as chemotherapy or corticosteroid use, its association with Botox injection is poorly documented. Case Presentation A 33-year-old woman presented with progressive painful rashes and vesicles on her forehead, scalp, and right upper eyelid, accompanied by fever and malaise following a Botox injection to treat wrinkles. A positive Tzanck smear test result confirmed the diagnosis of herpes infection. The patient was treated with antiviral medication, and her symptoms gradually regressed over several days. Conclusions Although herpes reactivation is more commonly associated with immunosuppressive therapies, few cases of herpes zoster and herpes simplex following Botox injection have been reported. The pathogenesis of herpes reactivation following Botox injection is unclear; however, it has been hypothesized that the Botox protein is a potent antigen that may activate the cellular immune system, making it easier for the virus to reactivate. Healthcare providers should be aware of this potential complication and consider it when evaluating patients who present with painful rashes following Botox injections. In addition, individuals who want to receive Botox injections should be informed of this complication. The diagnosis of herpetic infection should be made promptly, and antiviral therapy should be initiated to minimize the risk of complications. Further research is needed to better understand the pathogenesis and risk factors for herpes following Botox injection and to develop strategies for preventing and managing this complication.